PEMERIKSAAN DAN PERAWATAN SPA KAKI DIABETIK BAGI PENDERITA DIABETES MELLITUS TIPE 2 DENGAN RESIKO LUKA PADA KAKI: Care, Diabetic Foot, Diabetes Mellitus - Muhammad Basri; Najman Najman; Kistan Kistan (Politeknik Negeri Sriwijaya, 2023)
The main problem experienced by people with diabetes mellitus is the presence of acute and chronic complications that can aggravate health problems. One of the health problems due to Diabetes Mellitus is amputation due to hyperglycaemia conditions which can interfere with leucocytes as macrophages, resulting in prolonged wound healing and will cause infection. This community service is an effort to care and prevent Diabetes Mellitus to the community by using education, demonstration and mentoring methods. The purpose of this activity is to increase the knowledge of the Paccing village community about Diabetes Mellitus and be able to apply diabetic gymnastics and diabetic foot SPA treatments. This activity includes three stages, namely Preparation, Implementation and Evaluation. The output of this activity is that there is an increase in knowledge before and after the intervention as many as 19 (54%) respondents in the low category, 14 (40%) respondents in the moderate category and 2 (5.7%) respondents in the high category while the data obtained after the intervention are 3 (8.6%) respondents in the low category, 18 (51.4%) respondents in the moderate category and 14 (40%) respondents in the high category. it is hoped that the results of this activity will become a recommendation for the Puskesmas and the local government to be followed up, especially regarding advanced care and treatment that suits the needs of people with Diabetes Mellitus.